Analisis Sitogenetika Pada Pasien Dengan Amenore Primer - ODILIA YULIANI SISTRI; EVA DIAH SETIJOWATI; HERNI SUPRAPTI; RETNO DWI WULANDARI (Universitas Hang Tuah, 2025)
Abstract Amenorrhea is defined as the absence of menstruation in women of reproductive age. It is called primary amenorrhea if a person has not menstruated until the age of 16 years with normal secondary sexual characteristics or until the age of 14 years but there are no signs of secondary sexual development. There are many factors that cause primary amenorrhea, such as pituitary/hypothalamic disorders, dysfunction and abnormalities of the vaginal and uterine outlets. These abnormalities are caused by abnormalities in the endocrine glands, genetic (genes and chromosomes), psychological, environmental and structural abnormalities. This study aims to determine chromosome analysis in patients with primary amenorrhea at the Medical Genetics Laboratory, Faculty of Medicine, Wijaya Kusuma University Surabaya. The study was an observational descriptive study. The population in this study were all medical records of primary amenorrhea patients and the samples in this study were medical records of patients with primary amenorrhea at the Medical Genetics Laboratory of the Faculty of Medicine, Wijaya Kusuma University Surabaya in 2018-2023 and met the inclusion and exclusion criteria. The inclusion criteria are as follows: patients with a history of primary amenorrhea and exclusion criteria are secondary amenorrhea (POF) Premature Ovarian Failure. From 75 samples of primary amenorrhea patients, 39 patients (52%) had normal karyotypes and 36 patients (48%) had abnormal karyotypes. The 36 patients with abnormal karyotypes can be classified into number abnormalities, structural abnormalities, and primary amenorrhea patients with 46.XY DSD karyotypes. The chromosome number abnormalities in the patients were 45.X (Turner syndrome) and Turner mosaicism. Structural abnormalities were chromosomal deletions, isochromosomes, and translocations.